The war of ethical worlds: why an acceptance of post-humanism on Mars does not imply a follow-up on Earth - Garasic, Mirko Daniel (Medicina e Morale, 2021)
Space bioethics, or the bioethical approach to space exploration, is still a very limited field that mostly spins off from debates that we are having on Earth already. When discussing hypothetical scenarios such as that of colonizing Mars or other planets we tend to filter such conceptualizations through the eyes of our earthly standpoint. Yet, by looking into some of the approaches that various Posthumanist scholars with different levels of space exploration enthusiasm propose, we should resist the temptation to establish or reinforce a continuity between the ethical standards applied on Earth and Mars (or other planets or contexts in Space that substantially differ from Earth). This temptation is indeed very strong in the current literature; hence it needs to be addressed so to help us not being deviated from understanding what Mars or space colonization might indeed imply for humanity. This paper wants to introduce to a wider audience the concern that it is of crucial importance to acknowledge that the exceptionality of the conditions occurring in space should not be used as a tool to lower our guard towards a mass implementation of societal, biological and ethical revolutions on this planet and our world as the result of maladapting states of exceptionality that might work well in space but have a much weaker ethical legitimacy on Earth.